782 The relationship between parenteral leucine intake and plasma leucine in very preterm infants dependent on parenteral nutrition. A systematic review. (17th August 2022) - Davies, Keziah; Morgan, Colin
Abstract : Aims: Very preterm neonates (VPNs) are dependent on parenteral nutrition (PN) from birth. Recent evidence from sick term infants indicates that immediate provision of parenteral amino acids (AA) may be harmful and increase the risk of sepsis. 1 The inhibition of autophagy, a catabolic process important in the developing immune system, has been proposed as a mechanism. Current parenteral AA formulations used routinely in VPN result in high plasma concentrations of essential AA (including leucine) above the normal reference range. 2 Leucine is known to be a potent activator of the mTOR pathway, which increases protein synthesis but inhibits autophagy. We have previously shown how a systematic review of published plasma AA data can be used to calculate the optimal (higher) neonatal PN content of a single deficient AA. 3 We adapted this methodology to investigate the relationship between PN leucine intake and plasma leucine levels in VPN. The aim was to quantify the relationship between parenteral leucine intake and plasma leucine concentration to allow the optimal (lower) leucine content of neonatal PN to be calculated. This would also provide a methodology to correct the overprovision of the other essential AA in neonatal PN. Methods: The four databases searched were Cochrane, PubMed, Scopus and Web of Science. The systematic review was prepared following PRISMA-P 2015 guidelines. The PICO format was used to develop the search strategy. The population of interest to this review was PN-dependent VPNs; dependency was defined as requiring a minimum of 7 days of PN. The intervention and comparator are low versus high parenteral leucine intakes expressed as either the percentage leucine content of the AA solution (%) or absolute leucine intake (mg/kg/d). The outcome measured was plasma leucine concentration (micromoles/L). All study designs were eligible for inclusion, except for review articles. Only articles which reported the actual parenteral AA intake and measured plasma leucine concentration after day 3 (72 hours) of PN were eligible. The data were obtained using a data extraction form designed for this review. Quality assessments using a custom-designed tool and the GRADE framework were performed. Results: Twelve articles met the inclusion criteria, which collectively studied 650 VPNs. The dose-concentration relationships of leucine content (%) and absolute leucine intake (g/kg/d) with plasma leucine concentration (micromoles/L) both showed significant, moderately positive correlations (p < 0.05), as shown in figure 1 . Regression analysis indicated that absolute leucine intake was the stronger predictor of outcome. Subgroup analysis indicated that neither the overall study design nor the analytical method used for AA analysis affected the plasma leucine level. Conclusion: There is a linear relationship between plasma leucine concentration and both percentage leucine content and leucine intake (mg/kg/day) in VPNs. This work indicates that the leucine content of future neonatal PN solutions should be reduced to 8-9g/100g AA to achieve plasma AA concentrations within the reference range. This methodology can be applied to all essential AA. References: Lancet Child & Adolescent Health, van Puffelen E et al. JPEN, Morgan, C. & Burgess, L Nutrition Reviews, Premakumar CM et al.